Nonlinear state observers and extended Kalman filters for battery systems - Rauh, Andreas; Butt, Saif S.; Aschemann, Harald (Zielona Góra: Uniwersytet Zielonogórski)
The focus of this paper is to develop reliable observer and filtering techniques for finite-dimensional battery models that adequately describe the charging and discharging behaviors. For this purpose, an experimentally validated battery model taken from the literature is extended by a mathematical description that represents parameter variations caused by aging.
Keywords: observers; state estimation; Riccati equations; extended Kalman filters; parameter estimation